UNCITRAL model law on international commercial arbitration : a commentary / Ilias Bantekas, Pietro Ortolani, Shahla Ali, Manuel A. Gomez, Michael Polkinghorne. - Bantekas, Ilias; Ortolani, Pietro; Ali, Shahla F.; Gomez, Manuel Alejandro; Polkinghorne, Michael (Cambridge University Press, 2020)
This book provides a comprehensive commentary on the UNCITRAL Model Law on International Arbitration. Combining both theory and practice, it is written by leading academics and practitioners from Europe, Asia and the Americas to ensure the book has a balanced international coverage. The book not only provides an article-by-article critical analysis, but also incorporates information on the reality of legal practice in UNCITRAL jurisdictions, ensuring it is more than a recitation of case law and variations in legal text. This is not a handbook for practitioners needing a supportive citation, but rather a guide for practitioners, legislators and academics to the reasons the Model Law was structured as it was, and the reasons variations have been adopted.